Examining The Model Of Islamic Bank Profitability: The Roles Islamic Social Responsibility, Firm Size, Leverage, and Board Size - Diah Sepni Andhari; Muhammad Muflih; Dian Imanina Burhany (Universitas Pendidikan Indonesia, 2022)
Purpose - Profitability is very essential for the Islamic banking industry to maintain a sustainable business at a global level. However, until now Islamic banking has not been able to generate profitability competitiveness against conventional banking. Meanwhile, the increased awareness of the importance of business social responsibility has led to increased attention towards social responsibility based on Islamic values (known as Islamic Social Responsibility) since it is believed to be able to boost the profitability of Islamic banking. This study aims to reveal the effect of firm size, leverage, and board size on Islamic social responsibility and the role of Islamic social responsibility in mediating the influence of these three factors on the profitability of Islamic bankingMethodology - Observing 14 Islamic banks in Indonesia, this study used SEM-PLS for data analysis. Findings - The results show that board size has a positive effect on Islamic social responsibility while Islamic social responsibility itself has a positive effect on the profitability of Islamic banking. In addition, Islamic social responsibility can play a good role in linking firm size, board size, and leverage with the profitability of Islamic banking. The implications (theoretical and managerial) of this study are described at the end of the